Gene Expression Analysis of Chondrogenic Markers in Hair Follicle Dermal Papillae Cells Under the Effect of Laser Photobiomodulation and the Synovial Fluid - Farivar, Shirin; Ramezankhani, Roya; Mohajerani, Ezedin; Ghazimoradi, Mohammad Hosein; Shiari, Reza (Journal of Lasers in Medical Sciences, 2019)
Introduction: Regarding the limited ability of the damaged cartilage cells to self-renew, which is due to their specific tissue structure, subtle damages can usually cause diseases such as osteoarthritis. In this work, using laser photobiomodulation and an interesting source of growth factors cocktail called the synovial fluid, we analyzed the chondrogenic marker genes in treated hair follicle dermal papilla cells as an accessible source of cells with relatively high differentiation potential. Methods: Dermal papilla cells were isolated from rat whisker hair follicle (Rattus norvegicus) and established cell cultures were treated with a laser (gallium aluminum arsenide diode Laser (λ=780 nm, 30 mW) at 5 J/cm2), the synovial fluid, and a combination of both. After 1, 4, 7, and 14 days, the morphological changes were evaluated and the expression levels of four chondrocyte marker genes (Col2a1, Sox-9, Col10a1, and Runx-2) were assessed by the quantitative real-time polymerase chain reaction. Results: It was monitored that treating cells with laser irradiation can accelerate the rate of proliferation of cells. The morphology of the cells treated with the synovial fluid altered considerably as in the fourth day they surprisingly looked like cultured articular chondrocytes. The gene expression analysis showed that all genes were up-regulated until the day 14 following the treatments although not equally in all the cell groups. Moreover, the cell groups treated with both irradiation and the synovial fluid had a significantly augmented expression in gene markers. Conclusion: Based on the gene expression levels and the morphological changes, we concluded that the synovial fluid can have the potential to make the dermal papilla cells to most likely mimic the chondrogenic and/or osteogenic differentiation, although this process seems to be augmented by the irradiation of the low-level laser.